Pelatihan Penggunaan Sistem Aplikasi Manajemen Prospek Donatur Pada Panti Yatim Indonesia (PYI) Bekasi - Hendharsetiawan, Andy Achmad; Fitriyani, Aida; Atika, Prima Dina (Journal Of Computer Science Contributions (JUCOSCO), 2023)
Information technology is a series of computer-based systems that can assist business processes in making decisions that affect an organization so that the organization is able to face challenges in the current era. It is time for all activities and activities to also take advantage of the latest technology-based information systems. As part of the community in an effort to carry out one of the Tri Dharma of Higher Education in the form of community service. This community service activity aims to collect data on prospects for orphanage donors, namely in the form of Donor Prospect Management Application System Training at the Duta Harapan Indonesian Orphanage (PYI) Bekasi City Branch. Donor prospects are usually obtained from donor search activities or donor prospects who contact the orphanage. By using this application system, the management or management of donor prospect data will be much more efficient and effective, namely from recording and reporting as well as data analysis. This application system simultaneously records donor data, namely data on prospects for donors who have the status of being donors or paying infaq which is urgently needed by the orphanage. The results of this training activity are felt to be useful for the orphanage to increase insight and knowledge as well as ease in carrying out daily controls or supervision as well as being beneficial to the running of daily operations.